Reward and compensation system on employee performance during pandemic Covid-19 - Nor Aishah, Abdullah Zam Zam (2022)
An employee is an organization's most asset. This is because employees' decisions or conduct will affect the organization's success or failure. The firm's management should motivate employees by providing them with the best possible compensation to assure their optimum performance. The purpose of this study was to examine the impact of reward and compensation on employee performance during pandemic Covid-19. A survey was distributed through online questionnaire focuses on employee in Negeri Sembilan especially in Kuala Pilah, Rembau and Bahau. A total of 157 data was collected and used for analyses purpose using linear regression. The findings of this study indicate reward has significant positive influence on employee performance during pandemic Covid-19 by using regression of coefficient (ß = 0.315, p > 0) However, compensation shows insignificant result in current study (ß = -0.061, p > 0). The implication, limitation and recommendations for future studies were further discussed.